Soil quality indicators in temperate forests of the Volcanoes Biosphere Reserve, Mexico - Cruz-Flores, Gerardo; Guerra-Hernández, Eloisa A.; Valderrábano-Gómez, Juan M.; Campo-Alvés, Julio (REVISTA TERRA LATINOAMERICANA, 2020)
Soil degradation and erosion decrease carbon content and soil quality due to changes in land use. In order to identify and recognize the best soil quality indicators and relate them to organic carbon content, this research was carried out in forests of the Volcanoes Biosphere Reserve. Twenty-six sites distributed from 2600 to 3800 m.a.s.l. were selected by collecting soil samples from 0 to -0.2 m for physical and chemical analyses and from 0 to -0.1 m for biochemical and biological analyses. The results showed pH, sand percentage; gravimetric water contents; organic carbon; exchangeable Ca+2 and K+; carbon microbial biomass; acid phosphatase activity; and presence/abundance of bacteria and algae as excellent partial indicators for evaluating soil quality (IpCS). With IpCS, total soil quality (CSTsum and CSTmul) was determined additively and commutatively showing similar tendencies; however, the additive model was better in showin that affected forests and secondary vegetation (2600 and 2700 m) have lower soil quality, while in middle and high fringe (3000-3300 m and 3600 m) with Abies forests and Abies-Pine mixed forests, soils had higher organic carbon content and high CSTsum and CSTmul values.